Structure and dynamics of investments in the economy of Kazakhstan - Tulebayeva, G. A. (Journal of Economic Research & Business Administration, 2015)
The Republic of Kazakhstan has great interest for foreign investors. Investment attractiveness of Kazakhstan market provide a set of access to natural resources, the value of the market, the strategic location of Kazakhstan, as well as a stable political situation and the availability of an appropriate legislative framework. For economic development of the state it is necessary to attract foreign investment in effective way, which is the foundation of one of the areas of mutually beneficial economic cooperation between the countries. With the help of foreign investment can improve the industrial structure of the economy of Kazakhstan, to create new high-tech production, modernize fixed assets and technically upgrade the many businesses that prepare professionals and workers, to introduce cutting-edge management, marketing and know-how, to fill the domestic market with quality domestic products at the same time increase in the volume of exports to foreign countries.